Application of photon detectors in the VIP2 experiment to test the Pauli Exclusion Principle. Issue 5 (May 2016) - Pichler, A; Bartalucci, S; Bazzi, M; Bertolucci, S; Berucci, C; Bragadireanu, M; Cargnelli, M; Clozza, A; Curceanu, C; De Paolis, L; Di Matteo, S; D'Ufflzi, A; et al.
Abstract: The Pauli Exclusion Principle (PEP) was introduced by the austrian physicist Wolfgang Pauli in 1925. Since then, several experiments have checked its validity. From 2006 until 2010, the VIP (Violation of the Pauli Principle) experiment took data at the LNGS underground laboratory to test the PEP. This experiment looked for electronic 2p to Is transitions in copper, where 2 electrons are in the Is state before the transition happens. These transitions violate the PEP. The lack of detection of X-ray photons coming from these transitions resulted in a preliminary upper limit for the violation of the PEP of 4.7 × 10 -29 . Currently, the successor experiment VIP2 is under preparation. The main improvements are, on one side, the use of Silicon Drift Detectors (SDDs) as X-ray photon detectors. On the other side an active shielding is implemented, which consists of plastic scintillator bars read by Silicon Photomultipliers (SiPMs). The employment of these detectors will improve the upper limit for the violation of the PEP by around 2 orders of magnitude.